Spaces of Test and Generalized Functions Related to Generalized Translation Operators - Berezansky, Yu. M.; Tesko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We present main recent results on the generalization of white-noise analysis related to a family of generalized translation operators.